Effectivity of Fentanyl 1 μg/kg.weight to Prevent Emergence Agitation After General Anesthesia with Sevoflurane in Pediatric Patients - Bernouli, Renny; Puspita, Yusni; Maas, Endang Melati; , Theodorus (Perdatin Pusat, 2015)
Emergence agitation (EA) is a postanesthetic problem that interferes a child’s recovery and presents a challenge in terms of assessment and management. Fentanyl, a potent opioid, are hypotetised can prevent emergence agitation after general anesthesia with sevoflurane in pediatric patients. In this experimental clinical trial double-blind study, 34 children (age 2–7 years old) underwent elective minor surgery under general anesthesia with sevoflurane were selected to have an intravenous fentanyl 1μg/kgweight versus placebo before the end of the surgery. On thirty minutes after anesthesia, we evaluated agitation incidence (based on WATCHA score ≥3) and side effects of fentanyl. Recovery characteristics, including awakening time, duration of agitation, pain scale using FLACC scale, and discharge time were also recorded. All datas were analised using SPSS 21 and significantly different if p<0,10. The incidence of agitation on fentanyl group are lower in fentanyl group than placebo (17,6% versus 52,9%) and statistically different (p=0,071The incidence of vomiting are similar (5,9%) and there are no significant difference in awakening time. Fentanyl 1 μg/kgweight intravenous are proven effective to prevent emergence agitation after awakening from general anesthesia with sevoflurane in pediatric patients